ENTREPRENEUR PROFILE AND SALES TURNOVER OF SMALL AND MEDIUM ENTERPRISES IN WESTERN KENYA - Nassiuma, Bernard Nassiuma; Masinde, Jamin Masinde; Chebii , Pamela Chebii; David Sergon, David Sergon (International Journal of Current Practice in Management and Leadership (IJCPML), 2023)
This study examines the relationship between entrepreneur profile group differentials and the sales turnover of small and medium enterprises (SMEs) in western Kenya. The study is based on primary data collected through a cross-sectional survey in the counties of Usain Gishu and Bungoma in western Kenya. The study uses probability sampling strategies and descriptive and non-parametric analysis to test four hypotheses through Kruskal Wallis tests. The findings suggest that entrepreneur profile group differentials significantly affect the sales turnover of SMEs in western Kenya. Moreover, education, work experience, and managerial competence are crucial in SME performance. The study contributes to the literature on entrepreneurship, particularly in the context of SMEs in developing countries. The findings could assist policymakers in formulating entrepreneurial policies and providing support to SMEs, which play a central role in the transition to a market economy through innovation, income generation, and employment generation.